Opinions of medical students and academic teachers on online learning - Gotlib, Joanna; Białoszewski, Dariusz; Mosiołek, Anna; Dąbrowski, Filip (Polish Journal of Public Health, 2012)
Introduction. Online learning has been introduced at an increasing number of university-level schools training future health-care specialists. Aim. The present study aimed to analyse the opinions of students and teachers on the introduction of e-learning at their University. Material and methods. The voluntary, anonymous survey involved 1528 students and 128 academic teachers from Medical University of Warsaw. Results. According to our findings 53% of the students use the computer while studying and 74% do not need additional training. Moreover, 55% of the teachers use the Internet for educational purposes and 65% provide students with class materials via the Internet. Fifty eight percent of the students and 54% of the teachers would like to participate in e-learning (p=NS). Conclusions. A vast majority of students currently have access to the Internet for studying, so, they already have the technical preparation for distance learning. It is necessary to improve students’ computer skills and their ability to use e-learning platforms to avoid a situation when insufficient skills would impede teaching and affect their perception of this modern form of education. The introduction of e-learning at medical universities should begin with general academic courses conducted in the form of lectures and seminars.